The relationship between ceo traits and firm performance : evidence from large and small Malaysian public listed companies / Muhammad Fitri Izzat Abdul Halim - Abdul Halim, Muhammad Fitri Izzat (Universiti Teknologi Mara Perlis, 2020)
The main objective of this research is to study the relationship between CEO traits and firm performance. The independent variables involved in this study are age, gender, cultural background, and tenure. The purpose of this research is to examine the relationship between independent variables and dependent variables; firm performance, hence the hypothesis is noted. There is control variable used like firm size measured by total market capitalization of the companies. This research is carried out by using annual report of the companies and Thomson Reuters Eikon Data Stream as a part of the methodology in gathering data. The sampling method of this research is done by selecting 30 companies from Bursa Malaysia and categorized as 15 large and small companies based on market capitalization. The total number of the observation are 110 CEO from large companies and 36 CEO from small companies. The data collected has been analyzed through Statistical Package for Social Science (SPSS). Statistical Package for Social Science (SPSS) is applied by the researchers to analyze the demographic data. The discussion of this research objectives and recommendation for future research were included in this research as well. As a result, CEO cultural background of large companies showed positive significant towards firm performance. However, CEO age is negative significant toward firm performance while another variable is not significant towards firm performance. For small firms, CEO tenure and firm size present positive significant with firm performance while another variable found insignificant.